Identifikasi Serangga Semak di Sekitar Taman Nasional Gunung Gede Pangrango - Hawa, Siti; Syarifah, Zahra; Azzahra, Lintang Aulia; Aulia, Hana Marva; Isfaeni, Hanum (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to identify the diversity of bush insects around Mount Gede Pangrango National Park. This study uses an explorative method with a qualitative descriptive approach. Data collection was carried out for two days using insect net and hand collecting techniques. The results of the study found 19 insect species from 4 different orders, namely: Lepidoptera, Diptera, Coleoptera, and Orthoptera. Morphological analysis shows variations in adaptation, such as: camouflage, antenna structure, and color patterns on the wings that support the ecology and role of insects in the ecosystem. This diversity reflects the importance of bush vegetation as a habitat supporting a balanced ecosystem. This study also revealed that several insect species have significant ecological value in the process of pollination and natural pest control. In addition, several species show unique morphological adaptations to survive in a dynamic bush environment. The insect species found have the potential as bioindicators of environmental health. This study also highlights the importance of bush vegetation conservation to support the sustainability of insect populations and maintain ecosystem balance. These findings provide a basis for further research on insect taxonomy and conservation in similar habitats.